The effect of variable gradients on pacing in cycling time-trials - Cangley, P.; Passfield, L.; Carter, H.; Bailey, M. (International Journal of Sports Medicine, 2011)
It has been reported that performance in cycling time-trials is enhanced when power is varied in response to gradient although such a mechanical pacing strategy has never been confirmed experimentally in the field. The aim of this study was, therefore, to assess the efficacy of mechanical pacing by comparing a constant power strategy of 255 W with a variable power strategy that averaged to 255 W over an undulating time-trial course. 20 experienced cyclists completed 4 trials over a 4 km course with 2 trials at an average constant power of 253 W and 2 trials where power was varied in response to gradient and averaged 260 W. Time normalised to 255 W was 411±31.1 s for the constant power output trials and 399±29.5 s for the variable power output trials. The variable power output strategy therefore reduced completion time by 12±8 s (2.9%) which was significant (p<0.001). Participants experienced difficulty in applying a constant power strategy over an undulating course which acted to reduce their time gain. It is concluded that a variable power strategy can improve cycling performance in a field time-trial where the gradient is not constant.